Fuzzy Logic Based Technique for Propeller Noise in Mechanical Structures - Sampath Dakshina Murthy, A; V.J. Raj Kumar, P; Pratap Das, Rudra; Koteswara Rao, S (International Journal of Engineering and Technology, 2018)
The determination of the propeller of submarines is of great importance particularly when the measurable parameters are not within the reach using the membership function concepts. The paper has a solution of certain conditions which are of practical resolve.Â Â